The trade-off of Vibrio parahaemolyticus between bacteriophage resistance and growth competitiveness - Zeng, Xiuxiu; Liang, Shanyan; Dong, Jiayi; Gao, Guosheng; Hu, Yaoren; Sun, Yuechao (Frontiers in Microbiology, 2024)
Vibrio parahaemolyticus is a food-borne pathogen, which is often isolated from various seafood products. In order to control this pathogenic Vibrio, bacteriophage has more advantages than antibiotics in aquaculture and food processing. In this study, two kinds of bacteriophages isolated from the offshore sediments samples showed narrow host range specificity. To resist bacteriophage infection, host genes often mutate and have a significant impact on their own metabolic activities. In this study, we found that with flaG gene (slight homology to N terminus of multiple flagellins) mutated, making the bacteriophage unable to absorb to the cell surface of the host.And, the growth competitiveness of the anti-phage mutant strain is lower than the wild-type strain. These results indicated that the fitness cost, including loss of the growth competitiveness, constitutes a barrier to the prevalence of these defense mechanisms. And the selection pressure on different anti-phage strategies depends on the trade-off between mortality imposed by bacteriophages and fitness cost of the defense strategy under the given environmental conditions. In conclusion, this study provides valuable insights into the phage-host interaction and phage resistance in Vibrio parahaemolyticus. Our study provided knowledge for the evolutionary adaption of bacteria against the bacteriophage, which could add more information to understand the phage resistance mechanism before applying in the industry.